2012
DOI: 10.1155/2012/359017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freezing Temperatures onMicrodochium majusandM. nivaleSeedling Blight of Winter Wheat

Abstract: Exposure to pre-emergent freezing temperatures significantly delayed the rate of seedling emergence (P < 0.05) from an infected and a non-infected winter wheat cv. Equinox seed lot, but significant effects for timing of freezing and duration of freezing on final emergence were only seen for the Microdochium-infested seed lot. Freezing temperatures of −5• C at post-emergence caused most disease on emerged seedlings. Duration of freezing (12 hours or 24 hours) had little effect on disease index but exposure to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In all experimental years, spring oats were the least damaged by seedling blight of all the species tested. Haigh and Hare (2012) have reported that disease symptoms did not occur on seedlings grown from the non-infected seed lot in vitro and the presence of Microdochium spp. was confirmed on seedlings from the infected seed lot.…”
Section: Resultsmentioning
confidence: 99%
“…In all experimental years, spring oats were the least damaged by seedling blight of all the species tested. Haigh and Hare (2012) have reported that disease symptoms did not occur on seedlings grown from the non-infected seed lot in vitro and the presence of Microdochium spp. was confirmed on seedlings from the infected seed lot.…”
Section: Resultsmentioning
confidence: 99%
“…It is also noteworthy that for these years, the studied soil samples from winter and early spring times did not contain the pathogen and plants were not chlorotic, hence, they were not physiologically exhausted. In plate experiments, the optimum temperature for growth of M. nivale are around −6.3 °C and −2.2 °C respectively [ 34 ].…”
Section: Discussionmentioning
confidence: 99%